An evaluation of the effectiveness of the English Upgrading program for TOEFL in an Indonesian university using the CIPP model - Labibatussolihah, Labibatussolihah; Adriani, Nour Muhammad (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
Human resources capacity building is a vital part of institutional development, especially in the educational field, such as the university. As an academic language, English skills are highly needed among lecturers to improve the quality of institutions in general. What is the effectiveness of an English preparation course for lecturers in an Indonesian university during the pandemic time? Using Stufflebeam's CIPP model, this study aims to measure the quality and make recommendations on what should be improved or changed from such activity. There were 25 participants, two tutors, and one program coordinator involved as an informant. An online questionnaire was administered, as well as an in-depth interview with the tutors, coordinator, and selected participants. The results show that (1) the context is suitable to the condition, resources, and needs of the institution as well as participants. (2) In the Input section, the curriculum and variations in learning methods need to be further developed. (3) In the process section, the obstacles faced were the lecturer's workload, which should be adjusted during the course to make them focus on the program. (4) In the product section, a high level of satisfaction was found among the participants, with an overall positive review of its merit. There is still room for improvement. One of them is to follow up on participants' progress after the program is ended. An evaluation sheet or survey should be administered after the program is finished to assess the quality of the tutors and participants' satisfaction with the training.